EVALUATION OF TURNAROUND TIME (TAT) OF CLINICAL LABORATORY EXAMINATIONS BASED ON REQUEST TIME AND RESULTSAS AN INDICATOR OF THE EFFICIENCY OF DIAGNOSTIC SERVICES AT ROYAL PRIMA HOSPITAL IN MEDAN - R. Raje Telegem; Chrismis Novalinda Ginting; Ali Napiah Nasution (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
Turnaround Time (TAT) is an important indicator for assessing the efficiency and quality of clinical laboratory diagnostic services because timely laboratory results support rapid clinical decision-making. This study aimed to evaluate the Turnaround Time (TAT) of clinical laboratory examinations as an indicator of diagnostic service efficiency at RSU Royal Prima Medan. A quantitative descriptive evaluative study with a retrospective approach was conducted using secondary data from the laboratory information system for the period March–May 2026. Samples were selected using systematic random sampling from laboratory examination records that met the inclusion criteria. Data were analyzed descriptively by assessing the mean, median, and proportion of examinations meeting the established hospital standard, as well as comparing TAT across service units. The results showed that the mean TAT was 151.13 minutes in the emergency department, 161.29 minutes in inpatient services, and 187.05 minutes in outpatient services. Based on the hospital standard of ≤120 minutes, only 11.2% of examinations met the standard, while 88.8% did not. The emergency department demonstrated the highest compliance at 17.5%, followed by outpatient services at 9.8%, while no inpatient examinations met the standard. Overall, TAT performance had not met the established standard, indicating the need for workflow optimization to improve diagnostic service efficiency and timeliness.